Analisis Perbandingan Efisiensi Teknis Tempat Pelelangan Ikan (TPI) Bondet Dan Karangreja di Perairan Cirebon - Didha Andini Putri; Andi Perdana Gumilang (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
Facilities at TPI is deemed very important for the fishermen and the fishery business, because the Fish Auction Place is one of factors moving and increasing business and welfare of the fishermen. The purpose of this research was to identify facilities and equipments, analyze efficiency of physical condition and comparing efficiency of TPI Bondet and Karangreja in Regency of Cirebon. This study used descriptive research method. The method analysis to measure of the fish auction efficiency used by KEP.01/MEN/2007 concern to Quality and Safety of Fish Product in Production Process, Cultivation and Distribution. The research result that TPI Bondet and Karangreja facilities that is in the form of TPI building and TPI Office, meanwhile for its equipments such as basket, auctioneer seat, handcart, weigh, loudspeaker and lamps are still less adequate. TPI Bondet and Karangreja are valued still not efficient, as there were still many variable not meet criteria in accordance with indicators. TPI Bondet is more superior with obtaining score 35, whereas TPI Karangreja obtained score 26, means it these two TPI enters category efficient enough TPI